Defect management process in the software testing / Khilman Mohd Mokhlas - Mohd Mokhlas, Khilman (Faculty of Information Technology and Quantitative Sciences, 2005)
This research is a descriptive research on defect management process in software testing. In practice, software testing is usually performance after code has been generated. But it has been observed that the later code has been defected, the more expensive it to fix. Software testing as a process of preventing defects from appearing in the product is building and the removal of every defect that, although best efforts. Defect management techniques can be either corrective or preventive with respect to a given phase of the software process. The purpose of this defect management is finally to improve the quality of the product to be buih. Working from literature and current information, research will find out the finding the defect management process in software testing, how it working, what the approach been used and impact defect management process in organization point of view. The research determines descriptive research on the defect management process in software testing, technique, risk and indicator has been used in defect management process has applied in organizations for preventing defect.